Development of the mentalizing network structures and theory of mind in extremely preterm youth. Issue 11 (16th April 2022) - Fu, Xiaoxue; Hung, Andy; de Silva, Aryanne D; Busch, Tyler; Mattson, Whitney I; Hoskinson, Kristen R; Taylor, Hudson Gerry; Nelson, Eric E
Abstract: Adolescents born preterm (<37 weeks of gestation) are at elevated risk for deficits in social cognition and peer relationships. Theory of Mind (ToM) is a complex form of social cognition important for regulating social interactions. ToM and the underlying mentalizing network continue to develop across adolescence. The present study recruited 48 adolescents (12–17 years old) who were either born extremely preterm (EPT; <28 weeks of gestation) or full-term (FT) at birth. Cortical thickness, gray matter volume and surface area were measured in four regions of the mentalizing network: the temporoparietal junction, anterior temporal cortex, posterior superior temporal sulcus and frontal pole (mBA10). We also assessed the adolescents' performance on a ToM task. Findings revealed both group differences and group-by-age interaction effects in the gray matter indices within the temporal lobe regions of the mentalizing network. The EPT group also performed significantly worse than the FT group on the ToM task. The cortical structural measures that discriminated the EPT and FT groups were not related to ToM performance. These results highlight altered developmental changes in brain regions underlying mentalizing functions in EPT adolescents relative to FT controls.